Application of Various Order Reduction Methodologies Over Power System Components - Choudhary, Amit Kumar; Nagar, Shyam Krishna (Elsevier B.V., 2015)
Study and analysis of highly interconnected electrical system is time consuming and difficult; and appearance of inner uncertainty, result in system complexity with higher order, posing a great challenge to both system analysts and control engineers. Simplification of such design to their lower order equivalent via order reduction accomplishes a good approximation to the system for analysis. This paper attempts to discuss few noteworthy approximation techniques relevant to power system components. The test result based on the error computation between the original and reduced systems through the varied algorithms validate the models obtained to be a good approximant.
Keywords: differentiation; direct truncation; gamma-delta approximation; order reduction; Power system design; uncertain system